Analysis of Factors Associated with Fasting Adherence Behaviour of Preoperative Patients - Taupik Rahman; Syamsul Arifin; Ardik Lahdimawan; Meitria Syahadatina Noor; Abdullah Oski Illiandri (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Patient compliance with preoperative fasting instructions is essential to prevent perioperative complications such as pulmonary aspiration, which can have a serious impact on patient safety during surgery. Several factors such as age, gender, education, and understanding of medical instructions are thought to play a role in patient compliance with preoperative fasting. This study aimed to evaluate the relationship between these factors and patient compliance in a hospital in Banjarmasin. This study used a quantitative observational analytic design with a cross-sectional approach, involving 75 elective surgery patients selected based on inclusion criteria. Data were collected through interviews and questionnaires covering demographic information, education level, understanding of medical instructions, and compliance with pre-surgical fasting. Data were analysed using the Chi-Square test and logistic regression. The results showed that age (p = 0.377) and gender (p = 1.000) had no significant association with adherence to preoperative fasting. In contrast, there was a significant association between education (p = 0.001) and understanding of instructions (p = 0.000) with adherence. Patients with higher levels of education and good understanding of instructions tended to be more compliant than patients with basic education and poor understanding. Patients who had a good understanding of instructions were 29.96 times more likely to adhere to preoperative fasting compared to patients with poor understanding. Understanding of instructions is the most dominant factor in influencing patient compliance. The analysis showed a B coefficient of 3.599 with an OR of 36.556 (p-value = 0.000). This means that patients who have a good understanding of instructions are 36.5 times more likely to adhere to preoperative fasting compared to those with poor understanding. Good understanding significantly increased the likelihood of compliance, emphasising the importance of effective communication and clear education to patients about medical instructions. In conclusion, education and understanding of medical instructions are important factors associated with adherence to preoperative fasting. Meanwhile, age and gender showed no significant influence on adherence. Therefore, increased patient education and better understanding of medical instructions should be the focus of interventions to improve patient compliance, especially for those with lower education levels. Keywords: Adherence, Preoperative Fasting, Education, Understanding, Demographic Factors